Uso de bolsa de feno slow feeder melhora bem-estar de equinos militares - Mayara Gomes Corrêa (2019)
Horse confinement is a common practice worldwide. However, the privation of grazing and social interaction can harm the welfare and induce undesirable consequences. With the hypothesis that increasing forage consumption time can produce improvements in welfare, the objective was to verify the effect of the implementation of a slow feeder hay bag on the ethogram, the motor activity, the heart rate, and the cortisol circadian rhythm of stabled horses. Seven healthy horses were kept exclusively in individual stalls being feed with pelleted feed, alfalfa hay and Tifton hay. Horses were evaluated before and during 10 days using a slow feeder hay bag for forage offer. For ethogram and forage consumption time evaluations, horses were monitored for 24 hours using infrared cameras. The motor activity and the heart rate were verified remotely, using pedometers and heart rate sensor. The cortisol circadian rhythm was calculated by the percent variance between morning and afternoon serum concentration. The cortisol circadian rhythm variation of 30% or less is indicative of poor welfare. The effect of time over variables was verified by paired Student's t or Student-Newnan-Keuls tests (P <0.05). Hay bag implementation increased alfalfa ingestion time on 87% (P = 0.006). At the end of the study, two of four horses stopped with coprophage and the mean (± SD) time performing abnormal behavior decreased from 130,6 (± 168,8) to 86 (± 140) minutes (P = 0.02). The mean cortisol circadian rhythm variation increased from 26% (± 24) to 58% (± 9) (P = 0.004), with an incidence of 4 horses with abnormal cortisol circadian rhythm at baseline and none at the end of the experiment. The motor activity was reduced from 574 (± 126) to 306 (± 167) steps per day (P = 0.05) and the heart rate did not vary. In conclusion, the adoption of a slow feeder bag, an available and low cost device, was effective in improving welfare in stabled horses.